Prereferral rectal artesunate and referral completion among children with suspected severe malaria in the Democratic Republic of the Congo, Nigeria and Uganda. Issue 5 (17th May 2022) - Brunner, Nina C; Omoluabi, Elizabeth; Awor, Phyllis; Okitawutshu, Jean; Tshefu Kitoto, Antoinette; Signorell, Aita; Akano, Babatunde; Ayodeji, Kazeem; Okon, Charles; Yusuf, Ocheche; Athieno, Proscovia; Kimera, Joseph; et al.
Abstract : Introduction: Children who receive prereferral rectal artesunate (RAS) require urgent referral to a health facility where appropriate treatment for severe malaria can be provided. However, the rapid improvement of a child's condition after RAS administration may influence a caregiver's decision to follow this recommendation. Currently, the evidence on the effect of RAS on referral completion is limited. Methods: An observational study accompanied the roll-out of RAS in three malaria endemic settings in the Democratic Republic of the Congo (DRC), Nigeria and Uganda. Community health workers and primary health centres enrolled children under 5 years with suspected severe malaria before and after the roll-out of RAS. All children were followed up 28 days after enrolment to assess their treatment-seeking pathways. Results: Referral completion was 67% (1408/2104) in DRC, 48% (287/600) in Nigeria and 58% (2170/3745) in Uganda. In DRC and Uganda, RAS users were less likely to complete referral than RAS non-users in the pre-roll-out phase (adjusted OR (aOR)=0.48, 95% CI 0.30 to 0.77 and aOR=0.72, 95% CI 0.58 to 0.88, respectively). Among children seeking care from a primary health centre in Nigeria, RAS users were less likely to complete referral compared with RAS non-users in the post-roll-out phase (aOR=0.18, 95% CI 0.05 to 0.71). In Uganda, among children who completed referral, RAS users were significantly more likely to complete referral on time than RAS non-users enrolled in the pre-roll-out phase (aOR=1.81, 95% CI 1.17 to 2.79). Conclusions: The findings of this study raise legitimate concerns that the roll-out of RAS may lead to lower referral completion in children who were administered prereferral RAS. To ensure that community-based programmes are effectively implemented, barriers to referral completion need to be addressed at all levels. Alternative effective treatment options should be provided to children unable to complete referral. Trial registrstion number: NCT03568344 ; ClinicalTrials.gov.